2013
DOI: 10.1080/13549839.2012.732050
|View full text |Cite
|
Sign up to set email alerts
|

Reducing carbon, tackling fuel poverty: adoption and performance of air-source heat pumps in East Yorkshire, UK

Abstract: Deploying heating technologies, such as air-source heat pumps (ASHPs), can respond to the dual challenges of tackling fuel poverty and reducing carbon emissions from domestic energy consumption. In the UK, ASHP performance has been found to be below design levels. Elements of three strands of literature – innovation diffusion, environmental psychology and neighbourhood effects – are combined to gain insights into why the adoption and performance of ASHPs are lagging policy targets and design potential. Evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…A theme mentioned by four respondents was a preference for lower temperatures in the bedroom when sleeping at night. This preference for lower temperatures when sleeping has also been noted by other researchers (Fell 2016;Owen et al 2012). Energy Efficiency (2019) 12:5-17Social rhythms and energy demand…”
Section: Household Thermal Routines As Described By Householderssupporting
confidence: 49%
“…A theme mentioned by four respondents was a preference for lower temperatures in the bedroom when sleeping at night. This preference for lower temperatures when sleeping has also been noted by other researchers (Fell 2016;Owen et al 2012). Energy Efficiency (2019) 12:5-17Social rhythms and energy demand…”
Section: Household Thermal Routines As Described By Householderssupporting
confidence: 49%
“…It is interesting to note that other research has found that even within -perception of impact varies, and correlates with their job satisfaction and their belief in their own expertise (Mahapatra et al, 2011). The ERYC scheme was designed to tackle fuel poverty in tandem with reducing carbon emissions (Owen et al, 2012). This primary focus led to advice being offered which reduced energy bills first, rather than ensuring emissions reductions, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…With an air source heat pump, a particularly bad experience of installation in terms of disruption and damage to property, led one building user to believe that there was no difference in energy consumption before or after and doubt as to whether the equipment was working properly at all. In comparison, another householder who found the installation process well managed, had affectionate feelings towards the new heating system and overlooked teething problems with operation as unusual occurrences, easily overcome [42].…”
Section: Installationmentioning
confidence: 99%